Grundlagen zur tribologischen Analyse von Endoprothesen = Principles of tribological analysis of endoprostheses - Kretzer, Jan Philippe (Der Orthopäde, 2012)
For the tribological characterization of artificial joints, various experimental methods are currently available. However, the in vitro test conditions applied are only comparable in a limited way and transferability to the in vivo situation is also restricted. This is due to the different wear simulation concepts used and partly insufficient simulation of clinical worst case situations. In the present paper current scientific methods and procedures for tribological testing of artificial joints are presented. In addition, the biological effects of wear products are described enabling clinicians to challenge tribological studies and to facilitate specific interpretation of scientific results taking the clinical situation into account.
Gesehen am 26.04.2018